Time - Goudsmit, Samuel A. (Samuel Abraham), 1902-1978.; Claiborne, Robert (New York, Time inc., 1966)
A comprehensive exploration into the many facets of time. Examines through text and photograph the concepts of measurement and use of timekeeping instruments in astronomy, physics, engineering, geology and biology.
Bibliography: p. 196.
Keywords: Time; Time